Economic policy in postwar Japan : growth versus economic democracy - Yamamura, Kōzō (Berkeley, CA : University of California Press, 2022)
Since the end of the Pacific War, Japan has, broadly speaking, pursued two economic policies: a ""democratization"" policy laid down by the Allied Powers, and subsequently a ""de-democratization"" policy formulated and vigorously pursued by the independent government. Yamamura here addresses himself to two central questions: What were the objectives and results of each policy? And why and how did the earlier one give way to the later? Yamamura never loses sigh.
1. The American Policy Of Economic Democratization -- 2. From Reform To Recovery -- 3. The Emergence Of The Japanese Policy -- 4. Disintegration Of The Antimonopoly Policy, 1953-1957 -- 5. Toward The Pro-monopoly Policy, 1958-1965 -- 6. The Visible Hand And Structural Changes -- 7. The Zaibatsu Question -- 8. Tax Policy For Economic Growth -- 9. Labor And Wage In The Postwar Growth -- 10. Conclusion
Includes bibliographical references and index.
In English.
Description based on online resource; title from digital title page (viewed on August 31, 2023)
JSTOR
Keywords: Japan -- Economic policy; World War, 1939-1945 -- Influence; Japon -- Politique économique.; Guerre mondiale, 1939-1945 -- Influence; NON-CLASSIFIABLE.; BUSINESS & ECONOMICS / General; Economic policy; Influence (Literary, artistic, etc.); Japan; 1939-1945